Preparation of MgO-CaO/SiO2 catalyst from dolomite and geothermal solid waste for biodiesel production - Nadia Taradissa Maheswari; Wahyu Fitriani; Luqman Buchori; Hantoro Satriadi; K Kusmiyati; Norzita Ngadi; Widayat Widayat (International Journal of Renewable Energy Development, 2023)
Energy demand will increase along with the increase in population. The current energy demand is dominated by non-renewable energy as it could reduce dependence on fossil energy sources; hence, it is imperative to be developed. Biodiesel with waste cooking oil as its raw material is one of the renewable energies currently being developed. Catalyst can be utilized to improve the quality of biodiesel product and process. The major content in solid waste of geothermal power plant is silica oxide, while dolomite contains magnesium oxide and calcium oxide. This study aims to test the MgO-CaO/SiO2 catalyst performance from geothermal waste and dolomite in biodiesel production. The results of catalyst characterization based on FTIR, SEM, and BET tests indicates a successful impregnation method in MgO-CaO/SiO2 catalyst production. The result shows that the best variable to produce biodiesel is at the ratio of MgO-CaO: SiO2 is 15:85. The conversion of biodiesel using this variable is 92.63%. The overall results of biodiesel obtained in this study have a good quality and is in accordance with SNI 7182-2015.